(untitled) (Journal of actual problems of jurisprudence, 2020)
Abstract. The article analyzes the Nelson Mandela Rules regarding updated standards for the treatment of prisoners. The new version of the Rules was approved in 2015. The purpose of the scientific article is to draw the attention of the legal community of Kazakhstan to changes in international standards and updates in the approach to the rights of prisoners. The first part of the article provides a general overview of the UN Standard Minimum Rules for Prison Staff when dealing with prisoners in nine areas of standards. In the second part, the authors carried out a scientific analysis of the changes made to this UN document and formulated preliminary conclusions on them. The third part of the article is devoted about the conceptual basics of implementation the minimum standards for the treatment of prisoners in the national sphere of Kazakhstan. The scientific and practical significance of the work lies in the scientific analysis of the content of the updated rules. The main results and conclusions of the authors are that the Nelson Mandela Rules are of great importance and have a significant impact on the development of policies, laws and practices of states around the world. In writing this article, methods of logic, formallegal and systematic research methods were used. The value of the article lies in the development of the problems of penitentiary science and law of Kazakhstan. The practical significance of the results of the work lies in the scientific substantiation of the possibilities of implementing the standards in question in the national system of Kazakhstan. Key words: Nelson Mandela Rules, International Legal Standards for the Treatment of Prisoners, Penal Institutions, International Penitentiary Law, Penal Legislation of Kazakhstan, Penal System of Kazakhstan.